2017
DOI: 10.1016/j.jid.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Misbalanced CXCL12 and CCL5 Chemotactic Signals in Vitiligo Onset and Progression

Abstract: Generalized nonsegmental vitiligo is often associated with the activation of melanocyte-specific autoimmunity. Because chemokines play an important role in the maintenance of immune responses, we examined chemotactic signatures in cultured vitiligo melanocytes and skin samples of early (≤2 months) and advanced (≥6 months) vitiligo. Analysis showed that melanocytes in early lesions have altered expression of several chemotaxis-associated molecules, including elevated secretion of CXCL12 and CCL5. Higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…In conclusion, these data support the findings of Rezk et al (2017) for a role of CXCL12 in the pathogenesis of vitiligo. Especially, its capacity to predict future disease progression in stable patients is promising.…”
supporting
confidence: 89%
“…In conclusion, these data support the findings of Rezk et al (2017) for a role of CXCL12 in the pathogenesis of vitiligo. Especially, its capacity to predict future disease progression in stable patients is promising.…”
supporting
confidence: 89%
“…Yet, CXCL12 -CXCR4 chemotactic axis was mostly associated with dissemination of cancers to the lymph node, bone, lung, brain, and liver (Sun et al, 2010, Teicher and Fricker, 2010). In the skin, CXCL12 expression was associated with skin-infiltrating dendritic cells, pericytes, endothelial cells and fibroblasts (Avniel et al, 2006, Rezk et al, 2017), as well as with emigration of dendritic cells from the cutaneous tissue (Kabashima et al, 2007). In fact, data presented by Ujiie et al also demonstrate that CXCL12 expression in the EB-affected skin is mostly associated with skin infiltrating cell.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question may lie within vitiligo-affected lesional and perilesional skin. We reported that vitiligo melanocytes express and secrete higher levels of CXCL12 (Rezk et al, 2017). Because melanocytes represent a small population of cells in the cutaneous tissue, it is unlikely that melanocyte-derived CXCL12 would have an impact on its systemic level.…”
Section: To the Editormentioning
confidence: 87%
“…Recently, we showed that elevated expression of CCL5 and CXCL12 in cutaneous melanocytes is associated with vitiligo onset and progression (Rezk et al, 2017). Extending this work to the systemic compartment, in the letter titled "Alterations of CXCL12 in Serum of Vitiligo Patients" Speeckaert and coauthors (2017) assessed CXCL12 level in the sera samples from nonsegmental vitiligo patients and correlated it with disease activity.…”
Section: To the Editormentioning
confidence: 99%